Influence of plant and residue age on attraction, acceptance and larval survival of the banana weevil Cosmopolites sordidus (Coleoptera: Curculionidae) - Masanza, M.; Gold, Cliford S.; Huis, A. van; Ragama, P.E. (Springer, 2009)
Laboratory trials were conducted in Uganda at the Kawanda Agricultural Research Institute to determine attraction, eclosion success and larval survivorship of the banana weevil Cosmopolites sordidus (Germar) on crop residues of different ages. In the first experiment, studies focused on different types and ages of residues of one susceptible highland banana clone ‘Nabusa’ (genome group AAA-EA). Corms attracted 65% of the test weevils, pseudostems 30%, while 5% were non-respondents. Oviposition levels and the number of eggs per female were higher on young than old corms. Eclosion rates of < 1-day-old eggs inserted into corm pieces of residues (cultivar ‘Kisansa’, genome group AAA-EA) declined from 66% in residues collected < 2 days after harvest (DAH) to 58% in residues collected >30 DAH. To assess immature survival, < 1-day-old 1st instar larvae were put on banana corms of suckers and crop residues of the cultivar Kisansa in single rearing chambers. The number of surviving individuals was recorded at 3-day intervals until adults emerged. Survivorship was 12% on sword suckers, 10% on maiden suckers and 7% on flowered plants; and 12% on residues collected < 2 DAH and 5% on residues collected >30 DAH. Larval duration and mean days taken for adult emergence increased with plant and crop residue age. Females emerging from the different plant and residues treatments were similar in weight. The data suggest that all aged residues are suitable hosts for C. sordidus, suggesting that sanitation practices should be implemented soon after harvest.